Impact of the driver's visual engagement on situation awareness and takeover quality. (May 2022) - Marti, Paul; Jallais, Christophe; Koustanaï, Arnaud; Guillaume, Anne; Mars, Franck
Highlights: Distraction during autonomous driving impairs the mental model of the situation. Building good situational awareness requires monitoring the road well before the takeover. The quality of the recovery is consistent with the level of situation awareness. When distracted at the time of the takeover request visual perseverance may occur. Helping the driver regain situation awareness prior to the takeover is essential. Abstract: During automated driving (SAE Level 3), drivers can delegate control of the vehicle and monitoring of the road to an automated system. They may then devote themselves to tasks other than driving and gradually lose situational awareness (SA). This could result in difficulty in regaining control of the vehicle when the automated system requires it. In this simulator study, the level of SA was manipulated through the time spent performing a non-driving task (NDRT), which alternated with phases where the driver could monitor the driving scene, prior to a critical takeover request (TOR). The SA at the time of TOR, the visual behaviour after TOR, and the takeover quality were analysed. The results showed that monitoring the road just before the TOR allowed the development of limited perception of the driving situation, which only partially compensated for the lack of a consolidated mental model of the situation. The quality of the recovery, assessed through the number of collisions, was consistent with the level of development of SA. The analysis of visual behaviour showed that engagement in the non-driving task at the time of TOR induced a form of perseverance in consulting the interface where the task was displayed, to the detriment of checking the mirrors. These results underline the importance of helping the driver to restore good SA well in advance of a TOR.